Dampak Perubahan Iklim terhadap Penurunan Pendapatan Petani - Putri Sinaga; Angelina Sipayung; Arma Fauziah; Putri Simanjuntak; Tumiar Sidauruk (Journal on Education, 2024)
Climate change due to global warming is inevitable and will have a broad impact on many aspects of life. Changes in rainfall patterns, increased frequency of extreme weather events, and rising temperatures and sea levels are serious impacts of climate change that affect the agricultural sector. For Indonesia, the threat of climate change has serious implications for the achievement of the Sustainable Development Goals. In Indonesia, changes in rainfall due to climate change disrupt water supply to various sectors, including agriculture. This is evident from the fact that the area of land that was previously suitable for rice cultivation decreased by 20% between 1990 and 2009. Changes in rainfall patterns that result in the transition of the dry season and rainy season make current rice cultivation patterns no longer suitable as they used to be.